2019
DOI: 10.1155/2019/7647091
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique of Oophoropexy: Folding and Fixating of Utero-Ovarian Ligament to Round Ligament in a Patient with Reccurrent Ovarian Torsion

Abstract: Introduction Most cases of ovarian torsion occur in the reproductive age and many are related to ovarian and paraovarian masses. If it occurs without any subtle anatomic etiology or ovarian and paraovarian masses, recurrence of ovarian torsion is more likely. Recurrent left ovarian torsion is much less common than recurrent right ovarian torsion. The authors describe a rare case with their new ovarian fixation technique. Case and Method A 21-year-old female patient with polycystic ovarian syndrome had a 7th re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Recurrent right ovarian torsion is more common than the left side. [ 3 4 ] Rangaram et al . [ 1 ] reported a case of left adnexal torsion associated with left corpus luteal cyst.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recurrent right ovarian torsion is more common than the left side. [ 3 4 ] Rangaram et al . [ 1 ] reported a case of left adnexal torsion associated with left corpus luteal cyst.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cases occur in enlarged ovaries such as polycystic ovaries, ovarian cysts, para-ovarian cysts, or hyperstimulated ovaries preventing the return to the normal position after torsion. [ 3 5 ] Most of the cases with ovarian cysts or polycystic ovaries do not undergo torsion, which indicates the probability of other causes for the torsion. Further, torsion may occur in the presence of normal ovaries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent adnexal torsion can also be prevented by adnexal detorsion and shortening the utero-ovarian ligament. [ 15 , 21 ] Seven cases of ovarian torsion were reported by Hosny et al [ 22 ] ; 2/7 cases had OHSS, and 50% of the patients showed clinical symptoms and hemorrhagic cysts. Fortunately, there was no recurrence in these 2 patients, who underwent detorsion and oophoropexy.…”
Section: Discussionmentioning
confidence: 99%